2004
DOI: 10.1080/01459740490513521
|View full text |Cite
|
Sign up to set email alerts
|

Breathless in Houston: A Political Ecology of Health Approach to Understanding Environmental Health Concerns

Abstract: A political ecology approach to the study of environmental health problems can provide a comprehensive analytical framework with which to understand geographical and social disparities in health status. To date, however, political ecology has remained limited in its application to health problems, and where health has been addressed, biomedical models have prevailed, with little attention to differing explanatory models of health and disease. By integrating political ecology with an interpretive critical medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 17 publications
0
49
0
4
Order By: Relevance
“…There were media releases and warnings that parents should keep their children indoors, especially children prone to asthma. More ubiquitous forms of air pollution, including industrial and occupational dusts and chemicals, were less likely to make a headline than a volcano erupting -a point echoing Harper (2004) -but the causal narratives of some participants showed that these threats are highly significant when it comes to making sense of why one 'got' COPD.…”
Section: Wind and Breathingmentioning
confidence: 99%
See 2 more Smart Citations
“…There were media releases and warnings that parents should keep their children indoors, especially children prone to asthma. More ubiquitous forms of air pollution, including industrial and occupational dusts and chemicals, were less likely to make a headline than a volcano erupting -a point echoing Harper (2004) -but the causal narratives of some participants showed that these threats are highly significant when it comes to making sense of why one 'got' COPD.…”
Section: Wind and Breathingmentioning
confidence: 99%
“…The village only had electricity for 15 years and so like many villages in the interior, it had experienced dramatic transformation and modernization in the very recent past. As Harper (2004) reminds us, perceptions of risk when it comes to air are context specific. In Uruguay, it seemed the country and the city were increasingly connected by shared concerns about pollution, linked both to industrial development and agriculture.…”
Section: Wind and Breathingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although much of the political ecology literature has focused on natural resources such as water, minerals, and land, scholars have recently turned their attention to how power relations manifest in the air (Harper 2004;V eron 2006;Buzzelli 2008;Whitehead 2009). Much air pollution research focuses on the outdoors, but Biehler and Simon (2011) have called on geographers to examine the indoors as politicalecological spaces that are both socially produced and inextricably linked with the outdoors.…”
Section: Political Ecology Of Urban Air Pollutionmentioning
confidence: 99%
“…She uses political ecology to understand how structural inequalities cause uneven health outcomes, and anthropology to examine how cultural adaptations to environmental change affects health. Harper (2004) critiques medical anthropology for tending to treat the environment "in much the same way as political ecologists have treated health -that is, as a singular process affecting populations relatively evenly" (299). The key argument in this article is that "citizen perceptions of how various health problems are connected to the environment not only shape how they respond to illness but also influence how they interact with their environment" (Harper, 2004, 300).…”
mentioning
confidence: 99%